Determinants of Passenger Satisfaction at Terminal 3 of Soekarno-Hatta Airport - Sarwono Hadi Saputro; Siti Maemunah; Yuliantini; Lira Agusinta (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the influence of service quality, information quality, accessibility, and facilities on passenger satisfaction at Terminal 3 of Soekarno-Hatta Airport. The population of this research includes all passengers or users of Terminal 3, with data collected from January 2023 to December 2023. The sample consists of 182 respondents selected through purposive random sampling. The data collection instrument is a questionnaire, and data analysis is conducted using SPSS software through classical assumption tests and multiple linear regression analysis. The results show that service quality, information quality, and facilities have a positive and significant effect on passenger satisfaction, while accessibility does not have a significant impact. Based on these findings, it is recommended that the management of Terminal 3 continue to improve service quality, provide more accurate and relevant information, and ensure that facilities remain well-maintained and modern. Future research is encouraged to expand the scope of the study by adding other relevant variables, such as security aspects or the use of technology in airport.